THE SEVEN CAPITAL SINS - A PROFANATION OF FASHION (Fiep Bulletin - online, 2019)
Academic research inspired by the theme Seven Deadly Sins is meant to portray the relationship between action andsin through fashion costumes. The aesthetic and stylistic creation of the fashion addition under this theme intends to presentbroad models in such a way that the sensuality does not overlap the audacious expression of the personality and originality.
Keywords: Conceptual fashion; seven sins; religion